Determinants of Crypto Investment Decisions: Rational Behavior or Irrational Behavior? - Ni Made Sri Artini; Gede Sri Darma (Green Publisher Indonesia, 2024)
Cryptocurrency investment is a high-risk investment instrument. Currently, the phenome-non is that while cryptocurrency investment is considered high-risk, but the transaction values are increasing. This study examines the determinants of crypto investment decisions: whether they are driven by rational or irrational behavior, and it tests the moderat-ing role of social influence on these determinants. This research uses a quantitative meth-od and primary data from respondents who are crypto investors residing in Indonesia. The sample consists of 124 respondents, including 95 male and 29 female respondents. Statistical analysis includes Outer Model analysis, Inner Model analysis, and direct effects, as well as Moderated Regression Analysis conducted using SmartPLS4 software. The results indicate that crypto platforms and financial literacy have significantly impact on invest-ment decisions, while herding behavior and FoMO (Fear of Missing Out) do not have a significant impact on investment decisions. Social influence is able to moderate the effect of crypto platforms on investment decisions, but it does not moderate the effects of finan-cial literacy, herding behavior, and FoMO on investment decisions. This study employs a research model that combines technological factors and psychological factors with exter-nal factors as moderating variables in crypto investment, making it important to contribute to the literature. This research implies an increase in awareness and understanding among investors regarding their investment decisions, enabling more rational choices, especially considering that crypto is a high-risk investment. Recommendations for future research include developing subsequent research models that can represent the determi-nants of crypto investment decisions using other variables.